2010
DOI: 10.1038/nature08811
|View full text |Cite
|
Sign up to set email alerts
|

Coherently wired light-harvesting in photosynthetic marine algae at ambient temperature

Abstract: Photosynthesis makes use of sunlight to convert carbon dioxide into useful biomass and is vital for life on Earth. Crucial components for the photosynthetic process are antenna proteins, which absorb light and transmit the resultant excitation energy between molecules to a reaction centre. The efficiency of these electronic energy transfers has inspired much work on antenna proteins isolated from photosynthetic organisms to uncover the basic mechanisms at play. Intriguingly, recent work has documented that lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

56
1,732
2
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,537 publications
(1,797 citation statements)
references
References 30 publications
56
1,732
2
7
Order By: Relevance
“…This idea found further support in a subsequent series of measurements that showed spectral beatings for cryptophyte algae [3] and Photosystem II protein complexes [9], indicating that coherent behavior in biological systems is ubiquitous. For FMO, the oscillations were found to persist for hundreds of femtoseconds at ambient temperatures and even up to a few picoseconds at 77 K [10].…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…This idea found further support in a subsequent series of measurements that showed spectral beatings for cryptophyte algae [3] and Photosystem II protein complexes [9], indicating that coherent behavior in biological systems is ubiquitous. For FMO, the oscillations were found to persist for hundreds of femtoseconds at ambient temperatures and even up to a few picoseconds at 77 K [10].…”
Section: Introductionmentioning
confidence: 69%
“…The signatures of vibronic coupling in multidimensional spectroscopy have drawn great interest lately, in particular to interpret oscillatory transients observed for light-harvesting complexes [3,[8][9][10] that persist much longer than predicted electronic dephasing times [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,10 Another new class of applications of classical MD is the elucidation of experiments in ultrafast electronic spectroscopy of biomolecules. It was recently shown that long quantum coherences can be observed in biological molecules [11][12][13] and the aim of atomistic simulations is to explain how the (classical) environment can influence the (quantum) evolution of the electronic states. [14][15][16][17][18] Also for the applications in photobiology, MD simulations are often coupled with electronic structure methods to describe aspects of the quantum dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Yz, 78.47.nj, 05.60.Gg Long-lasting oscillatory signals in optically excited light-harvesting complexes (LHCs) point towards the prevalence of a coherent electronic dynamics in molecular networks at physiological temperatures [2][3][4][5]. The experiments probe the electronic dynamics using twodimensional (2d) echo-spectroscopy for a series of delaytimes between the excitation pulse and the probe pulse.…”
mentioning
confidence: 99%